A structured approach to defect data management for improving DFM implementation in aerospace manufacturing. (2017) - Souri, Mohammed El; Gao, James; Owodunni, Oladele; Simmonds, Clive; Martin, Nick
The aim of adopting product lifecycle management in a highly product centric knowledge environment is to reduce product development time and costs whilst improving quality through integrating people, processes, resources and information effectively. In the aerospace industry, most products and systems are manufactured, delivered to customers and serviced over an extensively long time, typically 20 years or more. This results in the build-up of large amounts of dispersed data and information related to defects throughout the different product's lifecycle stages, hence inhibiting the ability to make effective use of defect data to improve design for manufacturing (DFM) implementation. There have been very limited research efforts aiming to overcome these challenges in the low volume high value aerospace manufacturing context. This paper presents the findings of an extensive industrial investigation carried out at BAE systems (Rochester, UK) to identify the gaps and requirements in the industrial practice and proposes the need for a structured approach to defect data management in order to establish the systematic link between the defects, engineering data, and related issues within PLM system context.